Aplikasi Mata Kuliah Matematika Ekonomi Bagi Mahasiswa Program Studi Ekonomi Berbasis Web - Syafrudin Abdie; Catur Sudarmadi (CV. Ulil Albab Corp, 2023)
The purpose of this study is the creation of a learning media web-based economic mathematics course, resulting in a learning media that is more interesting, attractive and accurate for users so that it can be used as a choice of learning media in the teaching and learning process, inspiring lecturers to use web media in the teaching and learning process and students can study anywhere without being limited by space and time. The software used in this application is moodle, xampp and internet) Keywords: e-learning, website